Targeted characteristics and use of socially marketed preventive health goods: evidence from condoms in sub-Saharan Africa. Issue 52 (8th November 2018) - Wilson, Nicholas
ABSTRACT: Social marketing is a popular method for allocating targeted publicly funded preventive health goods in poor countries. However, low demand among targeted groups may inhibit take-up relative to non-targeted groups, ownership may not result in use, and there exists little large-scale evidence on how use of socially marketed goods varies by targeted characteristics. I assemble national household survey data from 27 sub-Saharan African countries to examine how use of one of the most common socially marketed preventive health goods (i.e. male condoms) varies by the main targeted characteristics (i.e. low income, low educational attainment, and high HIV risk). The results suggest that the majority of condoms used are socially marketed condoms, engaging in transactional sex is associated with an increased likelihood of using a socially marketed condom brand, and low-income/low educational attainment are not associated with increased likelihoods of using socially marketed brands. The fact that distribution targets low socioeconomic status groups and relative use remains low suggests that weak demand for condoms among these groups inhibits use. Policymakers should consider mechanisms to increase demand and to further refine targeting efforts.